Falak Dan Ilmu Yang Berkaitan Dengannya - Muthmainnah Muthmainnah (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2016)
This paper confirms, through a literature review, that astronomy has been the concern not limited to its circle only. Many studies and scientific studies related to it co-developed the hisab and rukyat which became the main theme of its studies. Interdisciplinary studies in astronomy is revealed in the discourse of the Hijra calendar, among other things.